Strengthening Leadership and Islamic Work Ethics Through Employee Characteristics in Improving The Function of Risk Management in Bank SUMUT Syariah - Fahmi, Muhammad; Tarigan, Azhari Akmal; Sugianto, Sugianto (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
ABSTRACT   Purpose: The aim of this research is to examine and analyze the influence of leadership and Islamic Work Ethics through employee characteristics in improving the risk management function.Design/methodology: The population in the study used a purposive sampling method, consisting of 190 employees and all of them were used as the research sample. Of this number, 130 were research respondents. The analysis method used is SEM-PLS. Findings: Research findings show that Leadership influences Risk Management, Leadership mediated by Length of Work influences Risk Management, Islamic Work Ethic influences Risk Management, Islamic Work Ethic mediated by Length of Work influences Risk Management. This research recommends that leaders must be able to transform and invite employees to combine work for the good of this world and the hereafter.Practical implications: The Management of Bank Sumut Syariah (BSS) needs to implement Islamic Work Ethics (IWE) for its employees and implement more deeply factors such as justice, work is worship and achieving halal income.. Furthermore, the company organization has carried out Risk Management Certification (SMR) for its serving leaders. However, apart from SMR, BSS needs to consider implementing the ISO 31000 program regarding Risk Management, so that the risk management Originality/Value: The contribution of this research is that the emphasis on the element of religiosity in work is very necessary, because the foundation of Islamic Work Ethics is stronger than leadership.